Individual and combined roles of malonichrome, ferricrocin, and TAFC siderophores in Fusarium graminearum pathogenic and sexual development - Oide, Shinichi; Berthiller, Franz; Wiesenberger, Gerlinde; Adam, Gerhard; Turgeon, B. Gillian (Frontiers in Microbiology, 2015)
Intra- and extracellular iron-chelating siderophores produced by fungal nonribosomal peptide synthetases have been shown to be involved in reproductive and pathogenic developmental processes and in iron and oxidative stress management. Here we report individual and combined contributions of three of these metabolites to developmental success of the destructive cereal pathogen Fusarium graminearum. In previous work, we determined that deletion of the NPS2 gene, responsible for intracellular siderophore biosynthesis, results in inability to produce sexual spores when mutants of this homothallic ascomycete are selfed. Deletion of the NPS6 gene, required for extracellular siderophore biosynthesis, does not affect sexual reproduction but results in sensitivity to iron starvation and oxidative stress and reduced virulence to the host. Building on this, we report that double mutants lacking both NPS2 and NPS6 are augmented in all collective phenotypes of single deletion strains [i.e. abnormal sexual and pathogenic development, hypersensitivity to oxidative and iron-depletion stress], which suggests overlap of function. Using comparative biochemical analysis of wild-type and mutant strains, we show that NPS1, a third gene associated with siderophore biosynthesis, is responsible for biosynthesis of a second extracellular siderophore, malonichrome. nps1 mutants fail to produce this metabolite. Phenotypic characterization reveals that, although single nps1 mutants are like wild-type with respect to sexual development, hypersensitivity to ROS and iron-depletion stress, and virulence to the host, triple nps1nps2nps6 deletion strains, lacking all three siderophores, are even more impaired in these attributes than double nps2nps6 strains. Thus, combinatorial mutants lacking key iron-associated genes uncovered malonichrome function. The intimate connection between presence/absence of siderophores and resistance/sensitivity to ROS is central to sexual and pathogenic development.